2021
DOI: 10.31031/pprs.2021.04.000600
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of STIFIn Intelligence Test for Students’ Career Planning : An Introduction and Impact of STIFIn Approach

Abstract: This study aims to map students' intelligence in accordance with the human brain which consists of the sense of thinking, intuiting, feeling, and instinct, through the implementation of the STIFIn approach. This method was also used to help them determine their career path for optimal productivity, because in this era of 4.0 industrial revolution, students are required to upgrade their skills according to their talents and intelligence. This study therefore uses critical analysis studies in literature review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, the genetic basis applied was different from the genetic basis of this study, namely STIFIn-based genetics. Furthermore, even though in practice a number of schools have implemented the STIFIn concept in learning, but in application, the STIFIn concept was applied for incubating by dividing students into certain classes based on the similarity of IM types as an example of STIFIn for tahfids Qur'an (Baharun & Adhimiy, 2019); and the latest research related to the application of STIFIn in education (Yandri, et al, 2021) indicated that students who have taken the STIFIn test have an increased understanding of their potential and better understand the potential for career choices that suit themselves. The concept offered in this study was managerial and it is applicaple for EFL general classes, it does not need to divide students into classes according to a certain type of IM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the genetic basis applied was different from the genetic basis of this study, namely STIFIn-based genetics. Furthermore, even though in practice a number of schools have implemented the STIFIn concept in learning, but in application, the STIFIn concept was applied for incubating by dividing students into certain classes based on the similarity of IM types as an example of STIFIn for tahfids Qur'an (Baharun & Adhimiy, 2019); and the latest research related to the application of STIFIn in education (Yandri, et al, 2021) indicated that students who have taken the STIFIn test have an increased understanding of their potential and better understand the potential for career choices that suit themselves. The concept offered in this study was managerial and it is applicaple for EFL general classes, it does not need to divide students into classes according to a certain type of IM.…”
Section: Introductionmentioning
confidence: 99%